A comparative study of electrochemical and electrostatic doping modulation of magnetism in Fe3O4 via ultracapacitor structure. (9th November 2022) - Gu, Fangchao; Zhang, Leqing; Li, Zhaohui; Zhang, Jie; Pan, Yuanyuan; Li, Qinghao; Li, Hongsen; Qin, Yufeng; Li, Qiang
Abstract: Electric field control of magnetism can boost energy efficiency and have brought revolutionary breakthroughs in the development of widespread applications in spintronics. Electrolyte gating plays an important role in magnetism modulation. In this work, reversible room-temperature electric field control of saturation magnetization in Fe3 O4 via a supercapacitor structure is demonstrated with three types of traditional gate electrolytes for comparison. Different magnetization response and responsible mechanisms are revealed by Operando magnetometry PPMS/VSM and XPS characterization. The main mechanism in Na2 SO4, KOH aqueous electrolytes is electrochemical effect, while both electrochemical and electrostatic effects were found in LiPF6 organic electrolyte. This work offers a kind of reference basis for selecting appropriate electrolyte in magnetism modulation by electrolyte-gating in the future, meanwhile, paves its way towards practical use in magneto-electric actuation, voltage-assisted magnetic storage, facilitating the development of high-performance spintronic devices.